1994
DOI: 10.1088/0953-8984/6/44/012
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of the local structure around the tantalum atom in potassium tantalate

Abstract: The local structure around the Ta atom in potassium tantalate KTaO3 has been investigated using extended X-ray absorption fine-structure (EXAFS) measurements. EXAFS spectra near the Ta LIII edge were observed at 24, 40, 100, 150, 200, 250 and 298 K. The Debye-Waller factor has been analysed in detail as also have other local structure parameters. Anharmonicity of the thermal vibration of the Ta atom which is located at the centre of an oxygen octahedron is almost negligible below room temperature, while anisot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…The errors in part reflect the statistical uncertainties from fitting of the χ data using IFEFFIT. The six-fold oxygen coordination of Ta is consistent with structural data from various Ta-oxide materials [21][22][23][24] and with coordination of Nb in glasses of similar composition [3]. Next, we make a qualitative examination of the χ data and the Fourier transforms (FT) of the k 3 -weighted χ data of the XAS spectra measured from the Ta glass + H 2 O sample to 960°C and~0.6 GPa, shown in Fig.…”
Section: Exafssupporting
confidence: 72%
“…The errors in part reflect the statistical uncertainties from fitting of the χ data using IFEFFIT. The six-fold oxygen coordination of Ta is consistent with structural data from various Ta-oxide materials [21][22][23][24] and with coordination of Nb in glasses of similar composition [3]. Next, we make a qualitative examination of the χ data and the Fourier transforms (FT) of the k 3 -weighted χ data of the XAS spectra measured from the Ta glass + H 2 O sample to 960°C and~0.6 GPa, shown in Fig.…”
Section: Exafssupporting
confidence: 72%
“…Cubic KTaO 3 was used as the model for the local structure around tantalum in all of the crystalline KTN specimens. KTaO 3 is macroscopically cubic at all temperatures, and previous EXAFS studies have shown that the local structure of KTaO 3 is cubic at all temperatures . For the KTN compositions examined by EXAFS, there is very little distortion of the tantalum coordination environment. , …”
Section: Methodsmentioning
confidence: 64%
“…Rod et al (1988) observed using NMR that even in the cubic phase with a timescale t > 10 À7 s and T < 40 K, the Ta 5+ ions might be in a local non-cubic environment. In the EXAFS study Nishihata et al (1994) suggested that the anisotropy of the thermal vibration of the Ta atom in the (001) direction corresponds at low temperatures to the softening of the transverse optical phonon at the centre of a Brillouin zone. Some of these features have to result from the anharmonicity of the atomic displacements in KTaO 3 .…”
Section: Introductionmentioning
confidence: 99%